2016
DOI: 10.1016/j.molcatb.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of chitooligosaccharides by an immobilized enzyme in a dual-reactor system

Abstract: A chitosanolytic activity found in a commercial α-amylase from Bacillus amylolyquefaciens (BAN) was covalently immobilized onto glyoxal agarose beads (25% recovery of activity) and assessed for the continuous production of chitooligosaccharides (COS). The immobilization did not change the reaction profile (with chitotriose and chitobiose as major products, using chitosans of different polymerization and deacetylation degrees), but significantly increased the enzyme thermostability. A two-step process was propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 52 publications
0
22
1
Order By: Relevance
“…In a previous work, we demonstrated that a Carbo-Pack PA-200 column was appropriate for the separation of complex mixtures of COS in less than 30 min employing a diluted NaOH solution (4 mM) as mobile phase (Santos-Moriano et al 2016b). This method represented a significant improvement compared with previous chromatographic protocols to separate deacetylated or partially acetylated COS (Xiong et al 2009, Horsch et al 1996, Lü et al 2009.…”
Section: Quantification Of Cos By Hpaec-padmentioning
confidence: 97%
“…In a previous work, we demonstrated that a Carbo-Pack PA-200 column was appropriate for the separation of complex mixtures of COS in less than 30 min employing a diluted NaOH solution (4 mM) as mobile phase (Santos-Moriano et al 2016b). This method represented a significant improvement compared with previous chromatographic protocols to separate deacetylated or partially acetylated COS (Xiong et al 2009, Horsch et al 1996, Lü et al 2009.…”
Section: Quantification Of Cos By Hpaec-padmentioning
confidence: 97%
“…The binding chemistry between the amino groups of the protein and the glyoxyl moieties of the support is rather simple and gives rise to robust linkages between the enzyme and the carrier [25][26][27]. However, the immobilization must be performed at alkaline pH in order to deprotonate amino groups and thus enhance their nucleophilicity [28].…”
Section: Immobilization Of β-Galactosidase From B Circulans On Glyoxmentioning
confidence: 99%
“…The strategies for enzyme immobilization are commonly classified into three groups [18]: support binding (by adsorption or covalent linkages), entrapment and cross-linking. For reactions involving the transformation of carbohydrates, covalent binding is preferred over adsorption to avoid enzyme leakage [19], but most of the commercial activated carriers are expensive [20][21][22]. Cross-linking gives rise to biocatalysts with highly concentrated enzyme activity, significant stability and low production costs due to the absence of carrier, although the recovery of activity is commonly low [14,15].…”
Section: Introductionmentioning
confidence: 99%